2018
DOI: 10.1681/asn.2017080863
|View full text |Cite
|
Sign up to set email alerts
|

Macrophage Uptake of Necrotic Cell DNA Activates the AIM2 Inflammasome to Regulate a Proinflammatory Phenotype in CKD

Abstract: Nonmicrobial inflammation contributes to CKD progression and fibrosis. Absent in melanoma 2 (AIM2) is an inflammasome-forming receptor for double-stranded DNA. AIM2 is expressed in the kidney and activated mainly by macrophages. We investigated the potential pathogenic role of the AIM2 inflammasome in kidney disease. In kidneys from patients with diabetic or nondiabetic CKD, immunofluorescence showed AIM2 expression in glomeruli, tubules, and infiltrating leukocytes. In a mouse model of unilateral ureteral obs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
97
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 125 publications
(109 citation statements)
references
References 62 publications
4
97
0
Order By: Relevance
“…This format does not allow us to review this pathway in detail, as it has not been investigated in AKI yet. However, recent data suggest that it might be very important in AKI-chronic kidney disease (CKD) progression [2].…”
mentioning
confidence: 99%
“…This format does not allow us to review this pathway in detail, as it has not been investigated in AKI yet. However, recent data suggest that it might be very important in AKI-chronic kidney disease (CKD) progression [2].…”
mentioning
confidence: 99%
“…The role of these cytokines in driving CKD in an NLRP3‐dependent manner is well established , and the contribution of the AIM2 inflammasome in the production of these cytokines has only recently been suggested. This study demonstrated that Aim2 –/– macrophages that have engulfed necrotic cell DNA showed attenuated IL‐1β release . In this study, Aim2 –/– mice showed reduced renal injury, fibrosis and inflammation when compared with wild type littermates in a mouse model of unilateral urethral obstruction (UUO).…”
Section: Role Of Aim2 In Sterile Inflammatory Diseasesmentioning
confidence: 72%
“…Inflammasome‐dependent cytokines IL‐18 and IL‐1β are shown to be detrimental during CKD in a mouse model of IRI . DNA from necrotic cells in the kidney is recognized by AIM2, leading to assembly of an inflammasome complex to produce IL‐1β and IL‐18 from macrophages during the pathogenesis of CKD . Likewise, AIM2 provides an inflammatory feedback loop during the progression of cardiovascular and neuroinflammatory diseases .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations